IMPLEMENTASI AKAD HIWALAH SEBAGAI SOLUSI PELUNASAN UTANG DI BMT MITRA MANDIRI WONOGIRI - huda, Miftahul - (Universitas Muhammadiyah Surabaya, 2022)
The birth of a sharia-based economic system should be a solution to various economic difficulties of the community. But, many of default cases that led to the settlement in Wonogiri Religious Court seemed to show that the principles of Sharia Economic Law were not seen in hiwalah agreement at BMT Mitra Mandiri. Based on that, this research was limited to answer the following problems : (1) How is the implementation of the hiwalah agreement at BMT Mitra Mandiri Wonogiri? (2) What are the problems that often arise from the implementation of hiwalah agreement at BMT Mitra Mandiri Wonogiri? (3) How is the implementation of the hiwalah agreement at BMT Mitra Mandiri Wonogiri in accordance to Sharia Economic Law? The research data can be collected at BMT Mitra Mandiri Wonogiri, thus this research can be categorized as a Field Research. The results of this research are : (1) BMT Mitra Mandiri Wonogiri set the terms and condition as stated in the Sharia Economic Law. They used hiwalah bil ujroh agreement that performed by saying ijab and qabul, pronounced clearly without any coercion. The object of the agreement was not forbidden by sharia. (2) Â The problem that often arise was the customers did not fulfill their obligations. It was caused by uncertain economic conditions and the customers who like to delay payments. (3) the implementation of hiwalah financing was in accordance to Sharia Economic Law and the principles of tawhid, justice, maslahah, ta'awun, and caliphate.